The Risk of Chronic Gastrointestinal Disorders Following Acute Infection with Intestinal Parasites - Blitz, Jason; Riddle, Mark S.; Porter, Chad K. (Frontiers in Microbiology, 2018)
Background. Infectious gastroenteritis (IGE) is caused by numerous bacterial, viral, and parasitic pathogens. A history of IGE has been shown in previous studies to increase the risk of developing chronic gastrointestinal disorders and other chronic conditions. As bacteria and viruses represent the majority of pathogen-specific causes of IGE, post-infectious studies have primarily focused on these organisms. The objective of this study was to investigate an association between a history of parasite-associated IGE and the subsequent development of chronic post-infectious gastrointestinal and non-gastrointestinal disorders in a military population. Methods. International Classification of Diseases, 9th Revision Clinical Modification (ICD-9-CM) diagnostic coding data for primary exposures and outcomes were obtained for a retrospective cohort study of active component military personnel from 1998-2013. Exposed subjects consisted of individuals with documented infection with one of ten parasitic pathogens. Unexposed subjects were matched to exposed subjects on demographic and operational deployment history parameters. Adjusted odds ratios were estimated using logistic regression for several chronic disorders previously shown to be associated with a history of IGE. Results. A total of 896 subjects with a parasitic exposure were matched to 3681 unexposed subjects for multivariate regression analysis. Individuals infected with Balantidium coli, Ascaris lumbricoides, Strongyloides stercoralis, Necator americanus/Ancylostoma duodenale and Taenia spp had higher adjusted odds ratios (aOR) for development of several chronic gastrointestinal disorders when compared with unexposed subjects after controlling for various covariates. Conclusion. We found that parasite-associated enteric infection increases the risk of development of post-infectious chronic gastrointestinal disorders in a military population. These results require confirmation in similar populations and in the developing world where infection with these parasites is endemic. Further understanding of disease burden and causal mechanisms should direct primary prevention and potential disease interception strategies.